2008
DOI: 10.3310/hta12030
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of strategies for reducing fracture risk in children with juvenile idiopathic arthritis with additional data on long-term risk of fracture and cost of disease management

Abstract: BMD, adjusted for size, should be assessed as the primary outcome in studies of bone health in children with JIA. Quantitative computed tomography could be used where equipment is available as it offers the advantage of measuring volumetric density. Bisphosphonates are a promising treatment for osteoporosis in children with JIA, but the quality of the current evidence is poor. The accurate assessment of outcome is crucial. There are still uncertainties about the use of bisphosphonates in children, including wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 192 publications
0
13
0
Order By: Relevance
“…The main function of VDBP is to bind and transport vitamin D, which plays a major role in calcium homeostasis and bone turnover. A previous study postulated that children with some types of JIA may be at risk for bone fractures [74,75] and that VDBP was significantly overexpressed in polyarticular JIA patients [45]. Certain pro-inflammatory cytokines such as IL-1, TNF-, and IL-6 are increased in ERA subjects and are involved in the pathogenesis of various bone disorders [9,76].…”
Section: Discussionmentioning
confidence: 98%
“…The main function of VDBP is to bind and transport vitamin D, which plays a major role in calcium homeostasis and bone turnover. A previous study postulated that children with some types of JIA may be at risk for bone fractures [74,75] and that VDBP was significantly overexpressed in polyarticular JIA patients [45]. Certain pro-inflammatory cytokines such as IL-1, TNF-, and IL-6 are increased in ERA subjects and are involved in the pathogenesis of various bone disorders [9,76].…”
Section: Discussionmentioning
confidence: 98%
“…Some have suggested that interval monitoring of BMD may be more predictive of fracture risk, but acknowledge that this is unproven and could be misleading [30]. Other studies suggest that the use of the Z-score is more appropriate for younger patients, however, they are again limited in their evidence of fracture risk [31]. In addition, as T-scores are compared with a standard of healthy young individuals (age 20-29), Z-scores for young patients are, in general, identical to their T-scores, and thus provide little additional data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to the American College of Rheumatology, it is also indicated for the primary prevention of glucocorticoid-induced osteoporosis (6). In this context, attempts to extend the list of diseases, which would benefit from primary prevention with bisphosphonate treatment must be counterbalanced by considering an array of peculiarities and potentially negative issues: a) the mechanism behind bone loss, i.e., decreased bone formation or increased bone resorption, b) concerns exist about how long bone remodeling could artificially be inhibited by anti-resorptive drugs without serious impairment of bone repairing capacity (7), and c) the effectiveness of pharmacologic therapy in the prevention of osteoporosis in young individuals (8). …”
Section: Introductionmentioning
confidence: 99%